Pengaruh Ekstrak Biji Kedelai Putih (Glycine max) terhadap Waktu Kematian Cacing Gelang Babi (Ascaris suum) in Vitro - ., Pritami; Haryati, Sri; Sakiman, Bambang Sukilarso (Nexus Biomedika, 2013)
Background : White Soy beans (Glycine max) contain saponin and tripsin inhibitor that have been known having anthelmintic effect. This study aimed to determine the effect of White Soy beans extract toward death time of Ascaris suum, in vitro. Methods : The study was a laboratory experimental research using post â test only controlled group design. The subjects were an adult male and female worms (Ascaris suum) that their body length were around 15 cm â 35 cm. The sampling technique used was convenience sampling. The subject was arranged into 6 groups, each group consisted of 4 worms, replication was performed 4 times. NaCl 0.9 % and pirantel pamoat 5 mg/ml was added in the negative control group and in the positive control group, in a row.While white soy beans extract of concentration of 60%, 70%, 80%, and 90% w/v were added to the treatment group. Worms were immersed in 25 ml test solution and incubated at 37Â°C. The subjects were observed every 10 minutes and the number of dead worms was counted. Data were analyzed with linear regression and Pearson correlation. Results : The data of observation showed that total death mean time of Ascaris suum in the negative control and positive control were 2817.5 minutes and 42.5 minutes, while in the treatment group of concentration of 60% , 70% , 80% , and 90%Â w/v of white soy beans extract were 422.5 minutes, 370 minutes, 300 minutes, and 255 minutes, successively. The Pearson correlation test showed very close relationship between variation of the concentration and time of death worms (r = - 0.962). The linear regession test showed significantly (p<0.001) and the regression equation was Y = 2653.400 â 30.340 X and R square was 0.926. Conclusion : White soy beans (Glycine max) extract had effects to the mortality of Ascaris suum in vitro. The most effective white soy beans extract was 90% (w/v) although it was less effective than pirantel pamoat. Keywords : White Soy beans (Glycine max) Extract, Ascaris suum, death time.Â